Pelestarian Permainan Tradisional Melalui Program Pojok Bermain - Fauzi, Rafi Muhammad; Listiani, Risma; Ulum, Syahda; Haq, Siti Arinil; Afifah, Putri Jihan; Hamdan, Ahmad (Jurnal Ilmiah Pangabdhi, 2023)
The program deals with the preservation of traditional games. The development of an increasingly advanced era, especially in the aspects of science, technology, and communication, affects the culture of indonesia's younger generation. Young Indonesians are more familiar with mobile legend, free fire, and PUBG mobile games than traditional games such as hide and seek, pecle, congklak, clogs, and engrang which are the original culture of Indonesia. Therefore, we held a program using the medium of playing corner. The goal is so that children can understand the importance of preserving regional culture. The implementation of this program is in Diniyah Al-Furqan Kalimanggis Village, Manonjaya District, Tasikmalaya Regency with the target of children aged 5-12 years. The methods used in this program are lectures, conversations, interviews, practices, and tutoring. Aim to describe the facts. The source of data on the activities of this program is the result of field observations of activity participants. The result is that learners actively play and are able to play traditional games in the form of batok, clogs, hide and seek, and others. With the results of this program, participants of this activity spent their school holidays with positive things, namely learning and playing traditional games, children reacquainted with Sundanese culture and their social abilities increased judging by their courage in public speaking.